2020
DOI: 10.1002/cctc.202001314
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon and Soot Oxidation over Cerium and Iron Doped Vanadium SCR Catalysts

Abstract: V2O5−WO3/TiO2 (VWTi) catalysts are widely employed for selective catalytic reduction (SCR) of NOx. However, due to their poor thermal stability the application in diesel particulate filters (DPFs), i. e. 2‐way SCRonDPF is limited. In this study, the potential of Ce‐ and Fe‐doped VWTi systems for hydrocarbon and soot oxidation in addition to the SCR activity was systematically investigated for fresh and thermally aged samples. The formation of metal vanadates upon thermal aging, as identified by X‐ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
4
9
0
Order By: Relevance
“…At atmospheric pressure, the short chain model compound propylene had a minor effect on NOx reduction up to 400 °C. These findings agree with our previous studies [17,29] and also with those of Watling et al, [30] who showed an influence on NOx conversion only above the onset temperature of propylene oxidation. Hence, with increasing the temperature and especially the pressure, the negative impact on NOx conversion was enhanced.…”
Section: Impact Of Propylene On Nh3-scr Of Noxsupporting
confidence: 94%
“…At atmospheric pressure, the short chain model compound propylene had a minor effect on NOx reduction up to 400 °C. These findings agree with our previous studies [17,29] and also with those of Watling et al, [30] who showed an influence on NOx conversion only above the onset temperature of propylene oxidation. Hence, with increasing the temperature and especially the pressure, the negative impact on NOx conversion was enhanced.…”
Section: Impact Of Propylene On Nh3-scr Of Noxsupporting
confidence: 94%
“…In this context, several literature works reported that long-chain HCs are more effectively oxidized. 26,31,32 Even in the case of C 12 H 26 oxidation, from HC oxidation was higher than that of CO 2 (not shown in the figure). 31 As observed from Figure 21a, the introduction of dodecane under Standard SCR conditions led to a more pronounced inhibition effect of DeNOx activity with respect to what was previously described in the of C 3 H 6 .…”
Section: ■ Introductionmentioning
confidence: 82%
“…Several studies evaluated the DeNOx performances of typical V-based catalysts in the presence of C 3 H 6 . 11,25,28,31,32 In the work of Heo et al, 11 a commercial V 2 O 5 −TiO 2 sample had been tested. Figure 20 shows the effect of the cofeed of C 3 H 6 Different from Fe-and Cu-ZSM-5 (section 2 of this review), no significant effects of the cofeed of propylene were detected on the DeNOx activity at low temperature of the tested vanadiabased catalyst; however, at temperatures higher than 350 °C, NO conversion decreased with increasing C 3 H 6 concentration in the fed gas mixture.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discharge characteristics for all four V/M catalyst-packed DBD reactors are quite similar, it can be deduced that the physicochemical properties of V/M catalysts would play a significant role in plasma-catalytic soot oxidation in this work. A V/M catalyst with a higher SBET value would provide more adsorption and active sites for the heterogeneous catalytic reactions [35]. As the average diameter of soot in this work is much larger than the pore diameters of V/M catalysts, the active sites on the external surfaces of the V/M catalysts would be of great significance in soot oxidation.…”
Section: Effect Of Catalyst Support On Plasma-catalytic Soot Oxidationmentioning
confidence: 91%